Autologous fibroblasts for vocal scars and age‐related atrophy: A randomized clinical trial. (5th December 2019) - Ma, Yue; Long, Jennifer; Amin, Milan R.; Branski, Ryan C.; Damrose, Edward J.; Sung, Chih‐Kwang; Achlatis, Stratos; Kearney, Ann; Chhetri, Dinesh K.
Abstract : Objectives/Hypothesis: To assess the safety and efficacy of autologous cultured fibroblasts (ACFs) to treat dysphonia related to vocal fold scar and age‐related vocal atrophy (ARVA). Study Design: Randomized, double‐blinded, placebo‐controlled, multi‐institutional, phase II trial. Methods: ACFs were expanded from punch biopsies of the postauricular skin in each subject; randomization was 2:1 (treatment vs. placebo). Three injections of 1–2 × 10 7 cells or placebo saline was performed at 4‐week intervals for each vocal fold. Follow‐up was performed at 4, 8, and 12 months. The primary outcome was improved mucosal waves. Secondary outcomes included Voice Handicap Index (VHI)‐30, patient reported voice quality outcomes, and perceptual analysis of voice. Results: Fifteen subjects received ACF and six received saline injections. At 4, 8, and 12 months after ACF treatments, a significant improvement in mucosal wave grade relative to baseline was observed in both vocal scar and ARVA groups. Relative to control group, mucosal waves were significantly improved in the ARVA group at 4 and 8 months. Perceptual analysis significantly improved in the vocal scar group 12 months after ACF treatments compared to controls. Vocal scar group reported significantly improved vocal quality from baseline. VHI and expert rater voice grade improved in both groups, but did not achieve significance. No adverse events related to fibroblast injections were observed. Conclusions: In this cohort, injection of ACFs into the vocal fold lamina propria (LP) was safe and significantly improved mucosal waves in patients with vocal scar and ARVA. ACF may hold promise to reconstruct the LP. Level of Evidence: 1 Laryngoscope, 130:2650–2658, 2020